Béla Kerékjártó: (a biographical sketch) - Gáll, György (Teaching Mathematics and Computer Science, 2004)
Kerékjártó published more than 70 scientific papers mainly in the field of topology. He achieved his most important results in the classical transformation topology and in the theoretical research of the continuous groups. He was the author of three books: Vorlesungen über Topologie; Euclidean geometry; Study on the projective geometry.